L’apprentissage technologique dans les pays émergents - Rigas Arvanitis; Daniel Villavicencio; Zhao Wei (Revue d'anthropologie des connaissances)
This article proposes a theoretical reflection based on empirical investigations in Latin America and China in order to identify and characterize technological learning. After reviewing the literature on various approaches of learning in firms, we propose a definition of technological learning. Leaving aside the perspectives based on characterizations realized at the level of the firm, our interpretation differs from previous work in that it proposes to focus the analysis on the identification of internal and external technological activities and on joint knowledge qualified as “technical” rather than on management and commercial decision that target them. Grounding this view allows the re-examination of globalization and the appearance of innovative firms in emerging economies.